Mobile Health Insurance System and Associated Costs: A Cross-Sectional Survey of Primary Health Centers in Abuja, Nigeria - Chukwu, Emeka; Garg, Lalit; Eze, Godson (JMIR Publications, 2016)
BackgroundNigeria contributes only 2% to the world's population, accounts for 10% of the global maternal death burden. Health care at primary health centers, the lowest level of public health care, is far below optimal in quality and grossly inadequate in coverage. Private primary health facilities attempt to fill this gap but at additional costs to the client. More than 65% Nigerians still pay out of pocket for health services. Meanwhile, the use of mobile phones and related services has risen geometrically in recent years in Nigeria, and their adoption into health care is an enterprise worth exploring. ObjectiveThe purpose of this study was to document costs associated with a mobile technology-supported, community-based health insurance scheme. MethodsThis analytic cross-sectional survey used a hybrid of mixed methods stakeholder interviews coupled with prototype throw-away software development to gather data from 50 public primary health facilities and 50 private primary care centers in Abuja, Nigeria. Data gathered documents costs relevant for a reliable and sustainable mobile-supported health insurance system. Clients and health workers were interviewed using structured questionnaires on services provided and cost of those services. Trained interviewers conducted the structured interviews, and 1 client and 1 health worker were interviewed per health facility. Clinic expenditure was analyzed to include personnel, fixed equipment, medical consumables, and operation costs. Key informant interviews included a midmanagement staff of a health-management organization, an officer-level staff member of a mobile network operator, and a mobile money agent. ResultsAll the 200 respondents indicated willingness to use the proposed system. Differences in the cost of services between public and private facilities were analyzed at 95% confidence level (P<.001). This indicates that average out-of-pocket cost of services at private health care facilities is significantly higher than at public primary health care facilities. Key informant interviews with a health management organizations and a telecom operator revealed high investment interests. Cost documentation analysis of income versus expenditure for the major maternal and child health service areas-antenatal care, routine immunization, and birth attendance for 1 year-showed that primary health facilities would still profit if technology-supported, health insurance schemes were adopted. ConclusionsThis study demonstrates a case for the implementation of enrolment, encounter management, treatment verification, claims management and reimbursement using mobile technology for health insurance in Abuja, Nigeria. Available data show that the introduction of an electronic job aid improved efficiency. Although it is difficult to make a concrete statement on profitability of this venture but the interest of the health maintenance organizations and telecom experts in this endeavor provides a positive lead.